PTPN2 improved renal injury and fibrosis by suppressing STAT‐induced inflammation in early diabetic nephropathy - Li, Ya (J Cell Mol Med, 2019)
Diabetic nephropathy (DN) is a chronic inflammatory disease triggered by disordered metabolism. Recent studies suggested that protein tyrosine phosphatase non‐receptor type 2 (PTPN2) could ameliorate metabolic disorders and suppress inflammatory responses. This study investigated PTPN2's role in modulating DN and the possible cellular mechanisms involved. In a mouse model combining hyperglycaemia and hypercholesterolaemia (streptozotocin diabetic, ApoE(‐/‐) mice), mice showed severe insulin resistance, renal dysfunction, micro‐inflammation, subsequent extracellular matrix expansion and decreased expression of PTPN2. We found that mice treated with PTPN2 displayed reduced serum creatinine, serum BUN and proteinuria. PTPN2 gene therapy markedly attenuated metabolic disorders and hyperglycaemia. In addition, PTPN2 gene transfer significantly suppressed renal activation of signal transducers and activators of transcription (STAT), STAT‐dependent pro‐inflammatory and pro‐fibrotic genes expression, and influx of lymphocytes in DN, indicating anti‐inflammatory effects of PTPN2 by inhibiting the activation of STAT signalling pathway in vivo. Furthermore, PTPN2 overexpression inhibited the high‐glucose induced phosphorylation of STAT, target genes expression and proliferation in mouse mesangial and tubuloepithelial cells, suggesting that the roles of PTPN2 on STAT activation was independent of glycaemic changes. Our results demonstrated that PTPN2 gene therapy could exert protective effects on DN via ameliorating metabolic disorders and inhibiting renal STAT‐dependent micro‐inflammation, suggesting its potential role for treatment of human DN.